Penyuluhan Kewirausahaan dan Pemberdayaan Guru Serta Pegawai di Pondok Pesantren Ma’had Zaadul Ma’ad Palembang - Tika Handayani; Sunanto Sunanto; Adellia Suhermanto; Shally Rizkiyanti; Fepi Leisthari; Hidayah Aprini (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
Entrepreneurship is an important element in supporting economic independence and community empowerment, including in Islamic boarding school environments. This article describes the entrepreneurship outreach and empowerment program for teachers and employees of the Ma'had Zaadul Ma'ad Islamic Boarding School in Palembang. This program is designed to increase participants' understanding of the basic concepts of entrepreneurship, marketing strategies and small business management based on Islamic values. The methodology used includes lectures, discussions and evaluations to build a creative, innovative mindset and support economic independence. The results of the training showed high enthusiasm from participants in understanding the role of entrepreneurship as a strategic solution for developing the capacity of teachers and employees, as well as contributing to increasing the competitiveness of Islamic boarding schools. Key findings include the importance of entrepreneurial skills in creating a sustainable economic ecosystem, the relevance of business regulations, and strengthening collaboration between Islamic boarding schools and local communities. This program has had a significant positive impact, but further development is recommended